IMPROVING AND INCREASING THE EFFICIENCY OF EMERGENCY MEDICAL CARE (World Bulletin of Public Health, 2022)
Due to a single automated vertical control center in the work of the emergency medical service, the time for receiving calls has been reduced by three times, it is 8-12 minutes.
Keywords: Ambulance; Call-cente; Medical team of online consultations